2005
DOI: 10.1097/01.ccm.0000150958.20209.a3
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA expression of major histocompatibility complex class II genes in whole blood from septic shock patients*

Abstract: A global transcriptional down regulation of a gene panel required for MHC II-restricted antigen presentation may occur in the course of septic shock. Our results suggest that the transcriptional resumption of CIITA-regulated genes might contribute to the recovery of membrane HLA-DR expression observed in survivors. These results obtained at the mRNA level support previous reports describing the loss of monocyte HLA-DR at the protein level and thus confirm the potential of measuring monocyte HLA-DR in septic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
62
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 40 publications
16
62
1
Order By: Relevance
“…Decreased mHLA-DR was even found to be a better predictor of mortality than SAPS II and SOFA scores (110). In parallel, we demonstrated that the loss of mHLA-DR expression was due to a global regulation at the transcriptional level of all MHC class II restricted genes and that the magnitude of this regulation affected clinical outcome (111).…”
Section: Mhla-dr Expression and Clinical Studysupporting
confidence: 52%
“…Decreased mHLA-DR was even found to be a better predictor of mortality than SAPS II and SOFA scores (110). In parallel, we demonstrated that the loss of mHLA-DR expression was due to a global regulation at the transcriptional level of all MHC class II restricted genes and that the magnitude of this regulation affected clinical outcome (111).…”
Section: Mhla-dr Expression and Clinical Studysupporting
confidence: 52%
“…Levels of class II gene expression also vary in antigen-presenting cells dependent on particular stimuli. MHC class II gene expression may become markedly downregulated in particular physiological or disease states, for example, during severe or prolonged infection [26][27][28] or B-cell lymphoma 29 in which it is associated with poor outcome.…”
Section: Mhc Class II Genes and Their Expressionmentioning
confidence: 99%
“…The molecular mechanisms of HLA-DR downregulation at the surface of monocytes from critically ill patients are now better understood. HLA-DR production is impaired, and is retained intracellularly [7,8,9,10]. Interestingly, this monocyte phenotype can be reversed by the treatment of septic patients with interferon-γ or granulocyte-monocyte colony-stimulating factor [11,12,13].…”
mentioning
confidence: 91%